TAFSIR THEORY; STUDY ON AL-QUR`AN METHODS AND RECORDS. (TEORI TAFSIR; KAJIAN TENTANG METODE DAN CORAK TAFSIR AL-QUR`AN) - Sasa Sunarsa (Fakultas Agama Islam Universitas Wiralodra, 2019)
The interpretation method of the Qur'an is one way to study and understand the meaning and content of the verses of the Qur'an. Interpretation methods vary in model, form and approach. This erroneous understanding is the result of